NATIONAL IDENTITY IN THE CONDITIONS OF REGIONAL INTEGRATION: CASE OF SPAIN - I. . Prokhorenko (Ибероамериканские тетради, 2016)
The processes of regional integration transform the model of traditional territorial nation-state, create favourable conditions for building- up of new macropolitical (macroregional) identity, and change the existing multiple identity of individual and collective state and non-state political actors. National (or national-state) identity as self-identification of the citizens as collective members of national-state community turns out especially vulnerable in the issue of regionalization. European integration with its unique decentralized multilevel system of governance has given new areas of transnational political interaction for subnational actors, in the first place for regional authorities. Seeking to increase their own actorness at national and supernational levels, regional authorities of the EU member- states use including various instruments of mobilizing of the territorial consciousness and of politicization of the ethnicity, aggregating the interests of the territory. The Spanish case is interesting due que the political system of the country is localized, and the model of governance is multi-level. Spain as one of the oldest European state is an example of unaccomplished nation-building by virtue of territorial diversity and significant influence of regional nationalisms. The factor of European integration proves itself visually in relation to Spain, affecting in a variety of ways, directly and/ or mediately upon directions and dynamics of political processes of different levels in the country, mechanisms and instruments of interethnic relations and of immigration of different culture background, construction of new national-state identity during the post-Francoist period, rise of regional nationalism and particularism, specific character of postimperial identity.